1980
DOI: 10.1021/bk-1980-0127.ch020
|View full text |Cite
|
Sign up to set email alerts
|

Solute Permeation Through Hydrogel Membranes

Abstract: Poly(2-hydroxyethyl methacrylate) (p-HEMA) is a hydrophilic methacrylate polymer which was first prepared by Wichterle and Lim OJ.This polymer, and many other synthetic hydrogels, has been extensively examined for potential biomedical applications (2J.Although many studies have focused on the physicochemical nature of these hydrogels, many questions remain unanswered. Among these are the nature, organization, and role of water in determining such properties as interfacial and transport phenom ena.Problems whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 1 publication
(4 reference statements)
0
17
0
Order By: Relevance
“…To further clarify the pore mechanism, we studied the relationship between the drug diffusivity and the degree of hydration of the membranes (H) according to the free-volume theory. This theory has indicated that the relationship between drug diffusivity and membrane hydration could be written as following [35,36]:…”
Section: Diffusivity Studymentioning
confidence: 99%
“…To further clarify the pore mechanism, we studied the relationship between the drug diffusivity and the degree of hydration of the membranes (H) according to the free-volume theory. This theory has indicated that the relationship between drug diffusivity and membrane hydration could be written as following [35,36]:…”
Section: Diffusivity Studymentioning
confidence: 99%
“…Sarbolouki suggested that solute transport does not occur through membranes which contain only bound water in the absence of specific interactions 41 . Several gel researchers have adopted this idea although this effect has not been clearly demonstrated in gel systems 36,42 …”
Section: Permeabilitymentioning
confidence: 99%
“…For example, a partition coefficient greater than one hundred was reported for progesterone in a poly(hydroxyalkyl methacrylate) hydrogel film 37 . Kim et al studied permeation in poly(2‐hydroxyethyl methacrylate) (PHEMA) membranes, a relatively hydrophobic hydrogel widely used in biomedical applications 42 . Partition coefficients much greater than one (20 to 235) were reported for the hydrophobic solutes.…”
Section: Partition Coefficients Of Solutes In Gelsmentioning
confidence: 99%
“…In the partition mechanism, the solute transport is presumed to occur by a process involving the dissolution of the solute within the polymer followed by the diffusion through the membrane. 14 Conventionally, fluorinated copolymer hydrogels with high oxygen permeability for contact lenses are prepared by UV irradiation. [15][16][17][18][19][20] However, fluorinecontaining thermoreversible hydrogels have not been investigated in the literature.…”
Section: Introductionmentioning
confidence: 99%